Visual Impairment Secondary to Unilateral Isolated Epicapsular Star - Mehmet Serhat Mangan; Mehmet Erdoğan; Eray Atalay (Türk Oftalmoloji Dergisi)
We aimed to report a rarely observed case of unilateral epicapsular star and the visual impairment developed secondary to it. A 8-year-old girl presented with a complaint of blurred vision in the right eye; best-corrected visual acuity was 0.7 in the right eye and 1.0 in the left eye. Near visual acuity was J1 in the right eye and J1+ in the left eye. The patient had no systemic disease and no clinical findings such as ocular inflammation, trauma, or history of use of topical and systemic drug. On biomicroscopic examination, no pigment deposition was observed in the cornea of both eyes and anterior chamber was normal. The anterior capsule of the lens in the right eye demonstrated dense pigment depositions centrally which were obscuring the pupillary axis. Iris translumination defect was not seen. Gonioscopy was performed and no pigment deposition was seen in the iridocorneal angle. Fundus examination revealed no pathology in the vitreous, posterior pole, and peripheral retina. In the absence of signs of intraocular inflammation and other causes of primary or secondary pigment dispersion, it is likely that the pigmented cells were implanted on the lens surface in utero from the developing iris pigment epithelium. In such cases, visual impairment should be detected in early period, and the strict follow-up is of utmost importance. (Turk J Ophthalmol 2014; 44: 493-5)